A decision framework for orderly power utilization based on a computationally enhanced algorithm - Xu, Peng; Wang, Beibei (Frontiers in Energy Research, 2023)
In 2022, China faced unusually high temperatures leading to a lack of hydropower in the southwest and increased power demand in the east. This incongruity exerted substantial strain upon the power system. To tackle this, a structured method called Orderly Power Utilization (OPU) is suggested as an effective approach to manage short-term power shortages and prevent recurring blackouts. However, typical OPU strategies tend to overlook the principles of fairness, openness, and justice (OEJ), potentially causing problems for various users, especially major industries. Herein, this study introduces a comprehensive OPU framework. According to the demand difference in OPU plans in different periods, the optimization cycle is divided into several intervals to achieve computational enhancement. Furthermore, in the interest of judiciously managing the manifold OPU resources characterized by heterogeneous parameters, we introduce an aggregated operational model underpinned by the formalism of zonotopic sets.Numerical simulation results indicate the great potential of the proposed method to solve power shortage problems while upholding the imperatives of OEJ.